Why hackers win: power and disruption in the network society - Burkart, Patrick (University of California Press, 2019)
"When people think of hackers, they usually think of a lone wolf acting with the intent to garner personal data for identity theft and fraud. But what about the corporations and government entities that use hacking as a strategy for managing risk? Why Hackers Win asks the pivotal question of how and why the instrumental uses of invasive software by corporations and government agencies contribute to social change. Through a critical communication and media studies lens, the book focuses on the struggles of breaking and defending the 'trusted systems' underlying our everyday use of technology. It compares the United States and the European Union, exploring how cybersecurity and hacking accelerate each other in digital capitalism, and how the competitive advantage that hackers can provide corporations and governments may actually afford new venues for commodity development and exchange. Presenting prominent case studies of communication law and policy, corporate hacks, and key players in the global cybersecurity market, the book proposes a political economic model of new markets for software vulnerabilities and exploits, and clearly illustrates the social functions of hacking."--